Prabowo Speech After Determining as Presidential Election Results: Sociopragmatic Analysis - Harahap, Anggi Trinanda; Sari, Esti Swatika; Kusmiatun, Ari (East Asian Journal of Multidisciplinary Research, 2025)
This study aims to analyze speech acts, language varieties, and sociopragmatic aspects in Prabowo Subianto's victory speech within a sociopragmatic framework. The method used is quantitative content analysis, integrating the fields of pragmatics and sociolinguistics. The results of the analysis showed that in his speech, Prabowo used speech acts with declarative and imperative forms, as well as expressive, assertive, directive, and commissive types of speech acts. The functions include competitive, friendly, and collaborative. The use of language varieties is mainly formal, with the dominance of political and religious varieties. In the sociopragmatic context, Prabowo's speech shows an attempt to build an inclusive image, strengthen legitimacy, and emphasize the importance of unity in society. This research contributes to the understanding of political communication and its influence on society in a digital context.